Actions Taken After Getting Up Side Effects of Drug Post Vaccination Covid-19 In Bantimurung District Maros District - Ainayah, Ainayah Yuspian Putri; Rusli, Rusli; Ibrahim, Ismail (Journal of Health and Nutrition Research, 2023)
People who are willing to be vaccinated say that they believe vaccination can protect themselves, their families and others. Meanwhile, people who refuse vaccines have doubts about vaccines. Doubts that occur can be caused by the accuracy of the source of the information received. This study aims to determine the actions taken after getting drug side effects (ESO) after the covid-19 vaccination in Bantimurung District, Maros Regency. The research was conducted in April 2022. The type of research used is descriptive research. The population in this study were all people in Bantimurung District, Maros Regency. The sample in this study were people in Bantimurung District, Maros Regency who had received the vaccine. Calculating the size of the number of samples from a predetermined population can use the Slovin formula to obtain a sample of 100 people. Based on the results of the study, it is known that the actions taken by residents after they became aware of the side effects of drugs (ESO) after the Covid-19 vaccination in Bantimurung sub-district, Maros Regency, out of 100 people who were sampled, 59 people (59%) dominantly chose to take medicine. While 26 people (26.0%) chose to rest and 8 people (8.0%) chose to go to the hospital and 7 people (7.0%) chose to be alone. It is hoped that the government will increase the profile of information about the covid-19 vaccination program because one of the government's goals is to protect the community from transmitting the covid-19 virus